Analysis of the Prison Justice Reforms Act - Alisha, Tamil (International Journal of Law and Policy, 2023)
Purpose: The aim of the study is to analyze the Prison Justice Reform Act Methodology: This study adopted a desktop methodology. This study used secondary data from which include review of existing literature from already published studies and reports that was easily accessed through online journals and libraries. Findings: The study shows that rehabilitation and education programs were major reforms introduced in prisons. Rehabilitation programs aimed at enhancing job readiness, seeking skills, which equip the inmate with job search techniques and job behavioral health support. The study also shows that prison education programme was found to be of great benefit to the ex-convicts and the benefit trickle down to the community at large. Unique Contribution to Theory, Practice and Policy: The study was anchored on Cognitive behavior modification theory and legitimacy theory. The study recommended that prisons should focus on the importance of incorporating the knowledge of rehabilitation programs of initiative into the mainstream private sector and public policy decision making.